A study of influence of alkali cations on dialysis rate of nickel(II) sulfate - Handlířová, Marie; Macenauer, Jaroslav (Univerzita Pardubice, 1995)
The dialysis rate of nickel(II) sulfate in a stirred bath dialyser through the cation exchange membrane Nafion 427 has been measured using aqueous solutions of alkali sulfates or sulfuric acid as a stripping solution. The influence of stirring velocity in the feed and stripping solutions on the transport rate of nickel(II) cations through the membrane has been studied. The individual values of dialysis coefficients of the membrane have been evaluated using the Wilson diagram. The time dependences of concentration of nickel(II) cations have been measured spectrophotometrically at the wavelength of 394 nm. It has been concluded that the dialysis coefficients KMj (j = H+, K+, Na+, Li+) of the membrane depend on the character of the cations and follow the order KMH+ > KMK+ > KMNa+ > KMLi+. This order does not agree with the expected reverse order of the radii of cations. The change in the order of cations is connected with the hydration number of the cations.